2021
DOI: 10.3389/fneur.2021.765193
|View full text |Cite
|
Sign up to set email alerts
|

Top 100 Most-Cited Papers in Neuropathic Pain From 2000 to 2020: A Bibliometric Study

Abstract: Background: Neuropathic pain research has grown impressively in the past two decades, as evidenced by improvements in research quality and increments in the number of research papers. In views of this situation, the use of quantitative measurements to analyze and characterize existing research has become imperative. The aim of this research is to identify and analyze the 100 most-cited papers in neuropathic pain research.Methods: Neuropathic pain-related articles published between 2000 and 2020 were screened f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…Citation count analysis might be related to journal IF, publication frequency, and publication year. In general, an article with 100 or more citations is considered a "classic" in the research field and might even be a seminal paper (Xiong et al, 2021). However, our study showed that only 17 papers were cited more than 100 times, this can possibly come from the fact that comorbid epilepsy in AD may not be an interesting topic for The number of articles corresponding to different IF in the top 100 most-cited papers.…”
Section: Clinical Neurology 54mentioning
confidence: 70%
“…Citation count analysis might be related to journal IF, publication frequency, and publication year. In general, an article with 100 or more citations is considered a "classic" in the research field and might even be a seminal paper (Xiong et al, 2021). However, our study showed that only 17 papers were cited more than 100 times, this can possibly come from the fact that comorbid epilepsy in AD may not be an interesting topic for The number of articles corresponding to different IF in the top 100 most-cited papers.…”
Section: Clinical Neurology 54mentioning
confidence: 70%
“…Similarly, bibliometric analyses in other specific pain areas had shown the USA was the leader in pain research, such as pain in the elderly, 39 back pain, 40 acupuncture for low back pain, 41 and neuropathic pain. 42 Many of the most productive authors had been deeply involved in this field for more than ten years, reflecting the progressive development of their research. In recent years, Arendt-Nielsen L, as the most productive author, had contributed to elucidating the role of CS in tension-type headache, chronic neck and shoulder pain, pelvic pain, and osteoarthritis pain.…”
Section: Discussionmentioning
confidence: 99%
“…“Double blind” was also one of the most commonly used keywords in neuropathic pain research. 42 Besides, “central sensitization” was the research development trends and focus in the pain field after spinal cord injury. 37 Nowadays, there are a growing number of double-blind studies advancing the clinical application of the concept of CS, deepening the understanding of a variety of diseases such as osteoarthritis and migraine.…”
Section: Discussionmentioning
confidence: 99%
“…In light of document type, only articles and reviews were included; and the language was restricted to English only. Referring to other studies ( 13 , 14 ), two independent investigators reviewed the titles and abstracts and deleted studies that were not associated with epilepsy and suicide. After reviewing the titles and abstracts, 631 publications were remained.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 1, literature was retrieved online through the Science Citation Index-Expanded version of the Web of Science Core Collection (WoSCC). All data were acquired on December 16, 2021, so as to avoid the prejudice caused by the database update (11)(12)(13), and 1,107 results were produced.…”
Section: Methods Data Sources and Search Strategiesmentioning
confidence: 99%